Indeks Kepuasan Masyarakat Terhadap Layanan Perpustakaan Pusat Pendayagunaan Informatika dan Kawasan Strategis Nuklir BATAN - Suhendani Suhendani (Media Pustakawan, 2021)
The Library of Center for Utilization of Informatics and Nuclear Strategic Areas- National Nuclear Energy Agency (PPIKSN-BATAN) evaluates the library through a user satisfaction survey which is given directly to visitors who come physically to the library. This study aims to measure the user satisfaction index of the PPIKSN-BATAN library services. The method used is aquantitative research using the questionnaire. The research subjects were 60 people who had filled out a questionnaire on the aspects reviewed to determine user satisfaction with 9 service elements indicators. The results on the services quality got very good service quality with an IKM value of 3.48 (A) and a conversion value of 86.88. The elements of Complaint Handling, as well as Suggestions and Inputs, are the elements of the highest service value with a conversion value of 95.42 and an average IKM element of 3.82 (A) with very good service quality. Meanwhile, the element with the lowest index value is the element of Service Requirements Conformity with a conversion value of 80.83 and the average IKM element is 3.23 (B), but the service quality is still in the good category. User satisfaction with the service received gets an average IKM of 3.21 and a conversion value of 80.34 with good service quality. Overall, the service performance of the Library of PPIKSN-BATAN received a very good service quality score and user satisfaction with the information provided received a good response.